ECONOMIC CHALLENGES IN CAMBODIA AND VIETNAM - PRUM SOVANNKANNIKA (2021)
The purpose of this study is to emphasize the main economic crises, namely, the Global Financial Crisis and the ongoing economic threat of COVID-19 Crisis that immensely influenced the downward of FDIs, and the less demand oversea, declining exports in Cambodia and Vietnam. The study will discuss about the mechanisms made by both governments in responding toward the two crises. In fact, Global Financial Crisis caused negative effects towards five Cambodian major sectors and Vietnam’s two potential sectors. Initially, Cambodia’s FDIs faced dramatic losses. In the first 11 months of 2008, statistic showed a 12.5% drop in new construction investments. The sharpest drops were in projects funded with FDI. While in Vietnam, FDI faced a 50% drop estimated around US$ 6.5 billion resulted from the constraints of disposal capitals and the tightening of the world credit market. Secondly, Cambodia Institute of Development Study shown that the export sector contracted by 4% in 2008, losing US$129 million of export revenue, and was expected to continue shrinking in 2009 at a negative 2.5% growth and a loss in revenue of US$75 million. In Vietnam, in the fourth quarter of 2008, Vietnam’s export fell due to the direct and impacts of the global financial crisis with the downward its export. Vietnamese economic impact is clearly seen, especially in the tourism industry, which is among the most affected. Vietnam Airlines, the only national airline has reported that the damage from closing routes to be about US$ 1.3 billion. The study will indicate the keys mechanism from both governments in tackling crises. Cambodia and Vietnam introduced some similar methods during the 2008 crisis including fiscal policy, monetary policy, and exchange rate policy. During the COVID-19 economic threat, the countries have initiated two different mechanisms. In Cambodia, economic recovery plan focused on regenerating key affected sectors of the economy, optimizing and keeping borders open for trade, supporting a vibrant labor market and decent work, and diversification of the economy towards higher levels of value added production. The Vietnamese policy includes, supportive macroeconomic policies to ensure a resilient and inclusive recovery, sustained recovery attaches on financial stability, and decisive reforms in making the most considerable growth potential. Based on what have been critically discussed and synthesized, it can be concluded that the results of 2008 Global Financial Crisis and the economic threat of Covid-19 Crisis do not only influence and impact the developed world, yet its effects generate social and economic turmoil throughout the globe. With the result of globalization, especially economic cooperation, developing countries like Cambodia and Vietnam really faced difficulties in recovering their economies. In respond to the challenges, Cambodia and Vietnam have tried to initiate many economic policies in order to revive and boost their economic growth. As a result, Cambodia and Vietnam managed to escape, maintain the stability, and prosper theirs economy in a very tough, yet effective ways.